(3GdGfJUGQs - (3GdMSjfj GdbQTj, CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, (B436 (3g`s ((3eMeO Hf eMeO Hf MSf GdHQhLROgjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEfj eeJKd QSeg GdMVQj GdSGejI GdhRjQI GdYejOjI COGe Gddg SdWGfgG (B... (3GdJj TfY Ydi GdTjYI GdEeGejI hGOYi Ydjge eNGdaI GdELeGY (B...s
(3BNQgG (B:s
... (3ef JaVjd HYVge Ydi HYV aj GdLjGI HGdHQ hGdEMSGf dCf Pdc h Edi GdMSO hGdYOGhI hGdGNJdGa aj LhGR Pdc GdChd (B.(3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\278s
(3GdCYdGe (B4\278s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds